Belongingness, Universality, and Normalization within Reddit Mental Health Communities - Slobodian, Ryan; Boyce, Melissa; Roughley, Robert (Eximia, 2022)
Recently, a growing population has been accessing the social media platform, Reddit, for mental health support (Singer et al., 2014). The current study investigated Redditors' belongingness attitudes while participating in mental health subreddits compared to belongingness attitudes while interacting with offline support networks. Self-stigma and perceived-stigma attitudes of the participants (N = 512) were also assessed within the context of mental health subreddit participation, compared to stigma attitudes users felt offline. Findings suggest that participants felt significantly higher belongingness when interacting on mental health subreddits compared to offline networks. Self-stigma and perceived stigma were reduced when participants interacted on mental health subreddits compared to their offline network. The data indicated that higher belongingness on mental health subreddits significantly predicted lower perceived stigma levels. The results suggest that mental health subreddits may offer a positive, safe, anonymous, hopeful, supportive, and scientific environment for mental health discussion. Implications for clinical and counseling psychologists are discussed.